2013
DOI: 10.5249/jivr.v5i2.331
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on maxillofacial trauma conducted in Yamunanagar, India

Abstract: Abstract:Background:The Department of Oral and Maxillofacial Surgery, D.A.V [C] Dental College and Hospital, Yamuna Nagar, Haryana, India conducted a study on patients with maxillofacial fractures in a time span of seven years (2003-2010). The purpose of this study was to evaluate their aetiology, incidence, patterns and different modalities employed for management.Methods:In this study, 740 patients with 1054 fractures were evaluated clinically and radiographically, based on which closed reduction and open re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
76
6
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(122 citation statements)
references
References 28 publications
33
76
6
2
Order By: Relevance
“…Young adults between 20 and 35 years old also showed a high prevalence of OMF injuries, which is in agreement with similar studies describing prevalence between 27% and 58% [1,10,18,26,27,29]. Young adults have a higher exposure to risk factors, such as alcohol and drug use, and involvement with physical aggression [34].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Young adults between 20 and 35 years old also showed a high prevalence of OMF injuries, which is in agreement with similar studies describing prevalence between 27% and 58% [1,10,18,26,27,29]. Young adults have a higher exposure to risk factors, such as alcohol and drug use, and involvement with physical aggression [34].…”
Section: Discussionsupporting
confidence: 77%
“…The higher prevalence of cases in the afternoon and night shifts can be explained by increased active nightlife with gathering in clubs and bars, and the consequent increase in traffic, in addition to the fact that people are sleepier and prone to accidents [26]. Also in this sense, weekends are associated with higher consumption of alcohol and increased traffic due to family outings and sports practice [14].…”
Section: Discussionmentioning
confidence: 99%
“…Bali and Sharma [55] concluded in their study that mandible was the most commonly fractured bone with parasymphysis being the commonest affected site. In our study, condylar fracture was the most common fracture that occurred in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Subhashraj et al 13 reported that motorbike accidents are frequent in India due to socioeconomic conditions, speeding, and not wearing a helmet or safety equipment. Bali et al 14 reported that road traffic accidents being 71.9% are commonly in the 20 to 40 age group; most of them were driving two wheelers and mostly under the effect of alcohol. A total of 66.2% were on two wheelers, among whom 10% were wearing the helmet.…”
Section: Discussionmentioning
confidence: 99%